Development of a comprehensive protein microarray for immunoglobulin E profiling in horses with severe asthma. (20th August 2019) - White, Samuel; Moore‐Colyer, Meriel; Marti, Eliane; Coüetil, Laurent; Hannant, Duncan; Richard, Eric A.; Alcocer, Marcos
Abstract: Background: Severe asthma in horses, known as severe equine asthma (SEA), is a prevalent, performance‐limiting disease associated with increased allergen‐specific immunoglobulin E (IgE) against a range of environmental aeroallergens. Objective: To develop a protein microarray platform to profile IgE against a range of proven and novel environmental proteins in SEA‐affected horses. Animals: Six SEA‐affected and 6 clinically healthy Warmblood performance horses. Methods: Developed a protein microarray (n = 384) using protein extracts and purified proteins from a large number of families including pollen, bacteria, fungi, and arthropods associated with the horses, environment. Conditions were optimized and assessed for printing, incubation, immunolabeling, biological fluid source, concentration techniques, reproducibility, and specificity. Results: This method identified a number of novel allergens, while also identifying an association between SEA and pollen sensitization. Immunolabeling methods confirmed the accuracy of a commercially available mouse anti‐horse IgE 3H10 source ( R 2 = 0.91). Biological fluid source evaluation indicated that sera and bronchoalveolar lavage fluid (BALF) yielded the same specific IgE profile (average R 2 = 0.75). Amicon centrifugal filters were found to be the most efficient technique for concentrating BALF for IgE analysis at 40‐fold. Overnight incubation maintained the same sensitization profile while increasing sensitivity. Reproducibility was demonstrated ( R 2 = 0.97), as was specificity using protein inhibition assays. Arthropods, fungi, and pollens showed the greatest discrimination for SEA. Conclusions and Clinical Importance: We have established that protein microarrays can be used for large‐scale IgE mapping of allergens associated with the environment of horses. This technology provides a sound platform for specific diagnosis, management, and treatment of SEA.